Pengaruh Motivasi Kerja Dan Disiplin Kerja Terhadap Kinerja Karyawan Biro Umum Kementerian Keuangan Jakarta Pusat - Azzahra Haula Syafitri; Wiwin Wianti (Jurnal Riset Multidisiplin Edukasi, 2025)
Work motivation and work discipline are believed to have a positive and significant impact on the achievement of institutional goals. Optimal employee performance is the result of a balance between these two factors. This study aims to test simultaneously and partially the influence of work motivation and work discipline on employee performance. The hypothesis proposed is that there is a positive influence of both independent variables on the performance of employees of the General Bureau of the Ministry of Finance in Central Jakarta. The research method used a quantitative approach with a sample of 48 employees, consisting of 52% civil servants/state civil servants/public service contract employees and 48% temporary employees/interns. Data were collected through questionnaires and analysed using multiple linear regression analysis with the help of SPSS version 25. The regression analysis results showed that work motivation and work discipline together (simultaneously) had a positive and significant effect on employee performance, with a calculated F-value (17.140) exceeding the table F-value (2). Partially, work motivation had a positive and significant effect on performance (calculated T of 2.057 > table T of 1.679). Conversely, despite having a positive direction, work discipline partially did not show a significant effect (calculated T of 1.533 < table T of 1.679). These findings imply that for employees of the General Bureau of the Ministry of Finance in Central Jakarta, the motivation factor plays a more dominant and statistically significant role in improving performance compared to work discipline as an individual factor.